Focal Adhesion Protein Vinculin Is Required for Proper Meiotic Progression during Mouse Spermatogenesis - Petrusová, Jana; Havalda, Robert; Flachs, Petr; Venit, Tomáš; Darášová, Alžběta; Hůlková, Lenka; Sztacho, Martin; Hozák, Pavel (Cells, 2022)
The focal adhesion protein Vinculin (VCL) is ascribed to various cytoplasmic functions; however, its nuclear role has so far been ambiguous. We observed that VCL localizes to the nuclei of mouse primary spermatocytes undergoing first meiotic division. Specifically, VCL localizes along the meiosis-specific structure synaptonemal complex (SC) during prophase I and the centromeric regions, where it remains until metaphase I. To study the role of VCL in meiotic division, we prepared a conditional knock-out mouse (VCLcKO). We found that the VCLcKO male mice were semi-fertile, with a decreased number of offspring compared to wild-type animals. This study of events in late prophase I indicated premature splitting of homologous chromosomes, accompanied by an untimely loss of SCP1. This caused erroneous kinetochore formation, followed by failure of the meiotic spindle assembly and metaphase I arrest. To assess the mechanism of VCL involvement in meiosis, we searched for its possible interacting partners. A mass spectrometry approach identified several putative interactors which belong to the ubiquitin-proteasome pathway (UPS). The depletion of VLC leads to the dysregulation of a key subunit of the proteasome complex in the meiotic nuclei and an altered nuclear SUMOylation level. Taken together, we show for the first time the presence of VCL in the nucleus of spermatocytes and its involvement in proper meiotic progress. It also suggests the direction for future studies regarding the role of VCL in spermatogenesis through regulation of UPS.
Keywords: centromere synapsis; Spermatogenesis; Vinculin; spermatogenesis; Focal Adhesions; Centromere; zvířata; myši; ubiquitin–proteasome system; fertility; Mice; proteasomový endopeptidasový komplex; kinetochore; vinculin; Proteasome Endopeptidase Complex; Male; vinkulin; spermatogeneze; Animals; fokální adheze; mužské pohlaví; centromera